2017
DOI: 10.1111/polp.12197
|View full text |Cite
|
Sign up to set email alerts
|

Let Me Tell You a Little Bit about Myself: Biographical Appeals in Congressional General Election Campaign Advertising

Abstract: Political campaigns discuss the personal dimensions of their candidates with great frequency, but scholars of campaign message strategy have not addressed why and how campaigns do so. This project focuses on the use of biographical appeals in campaign advertisements. Employing a dataset of candidate-sponsored campaign advertisements in the 2004 House and Senate general election, we argue that campaigns use these appeals in an effort to develop and enhance the credibility and likeability of their candidate in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…When you look at Varadkar, contradictions are apparent: yes, he represents a new, progressive politics in the fact that he is a political leader who has "come-out" as gay. However, this image does not fit with the traditional "family values" trope, often utilised by right-wing politicians who play on this aspect of their identity as a mechanism to engender electoral support (Arbour & McGowen, 2017).…”
Section: Daragh Mcdermottmentioning
confidence: 91%
“…When you look at Varadkar, contradictions are apparent: yes, he represents a new, progressive politics in the fact that he is a political leader who has "come-out" as gay. However, this image does not fit with the traditional "family values" trope, often utilised by right-wing politicians who play on this aspect of their identity as a mechanism to engender electoral support (Arbour & McGowen, 2017).…”
Section: Daragh Mcdermottmentioning
confidence: 91%
“…Since its launch in 2007, Twitter has become a popular and easy way for politicians to directly communicate with constituents (Munger et al, 2016). Research to this point has found that Twitter is used by political elites to express partisan and ideological positions, share relevant policy information (Ballard et al, 2022(Ballard et al, , 2023Lee & Shin, 2012), and highlight personal stories (Arbour & McGowen, 2017;Lee & Oh, 2013;McGregor, 2018). The wide-ranging content broadcast by candidates and campaigns reflects their sensitivity to the varied types of information voters seek (Lipsitz et al, 2005).…”
Section: Theory and Previous Researchmentioning
confidence: 99%